A comparison of the type IX collagen levels of the intervertebral disc materials in diabetic and non-diabetic patients who treated with lumbar microdiscectomy - Kaplan, Metin; Arici, Lutfu; Ozturk, Sait; Simsek, Bengu Cobanoglu; Hergunsel, Omer Batu; Erol, Fatih Serhat (Springer, 2018)
The purpose of this study was to compare type IX collagen levels in the intervertebral disc (IVD) materials of diabetic and non-diabetic patients with lumbar disc herniation and to determine whether there is a relationship between diabetes mellitus (DM) and type IX collagen levels in degenerated discs. Overall, 30 non-diabetic patients and 30 type II diabetic patients who underwent lumbar microdiscectomy were included in this study. All patients underwent lumbar microdiscectomy, and IVD samples were obtained during the surgery. Deparaffinization, macroscopic digestion, and staining procedures were performed immunohistochemically. Fractional area stained, staining intensity, and total staining score were graded semi-quantitatively. The results were evaluated within a 95% confidence interval, and significance was evaluated as bidirectional at 0.05 and 0.01 significance levels. The type IX collagen staining intensities and fractional area stained were lower in the diabetic group than those in the non-diabetic group (p = 0.001). The total immunoreactivity staining scores of type IX collagen in the diabetic group were statistically lower at higher significance levels than the total immunoreactivity staining scores of type IX collagen in the non-diabetic group (p = 0.001). The duration of DM of the patients with DM was increased, the total immunoreactivity staining score of type IX collagen was decreased (p = 0.001). Diabetes reduces the type IX collagen level in the intervertebral disc and the duration of diabetes is the most important factor for this reduction. Diabetes may play a role in the development of disc herniation by reducing type IX collagen levels in the intervertebral disc. However, the causes of increased herniation in diabetic patients still have to be determined.
Keywords: Disc herniation; Diabetes mellitus; Collagen; Type IX; Microdiscectomy